AKTIVITAS ENZIM ASETILKOLINESTERASE PADA LARVA NYAMUK AEDES AEGYPTI DI KECAMATAN MEDAN AREA - RIDO RAIS HUTABARAT; NURFADLY . (LP2MTBM MAKARIOZ, 2020)
The epidemic of DHF are known to have occurred regularly over the last three centuries in tropical, subtropical andtemperate in all over the world. In Indonesia, DHF remains a serious problem and has become epidemic in a region for thelast 47 years. One of the efforts to control mosquito breeding is by eradicating adult mosquitoes using insecticides (fogging),but these efforts are often not right on target and the dose used is not appropriate. As a result, the mosquito are resistant toinsecticides. To determine the mosquito resistance against insecticides, one method that can be done is by doing abiochemical test which also knows the activity of the acetylcholinesterase enzyme in Aedes aegypti mosquito larvae.The method of this research is descriptive research with cross-sectional approach. The subject of research were 93 larvae ofAedes aegypti mosquitoes from several houses in the Medan Area District. The sampling technique uses total sampling.Acetylcholinesterase enzyme activity in 93 Aedes aegypti mosquito larvae was moderate activity, which was between 0.102to 1,254. There is Acetylcholinesterase enzyme middle state activity in Aedes aegypti mosquito larvae.